A self-disclosure model for adolescents with perinatally acquired HIV in Eswatini - Dlamini, Baliwe P.; Mtshali, Ntombifikile G. (Curationis (Pretoria), 2025)
Background Adolescents living with HIV (ALHIV) are faced with the hard decision of how to disclose their HIV status to others. Despite this obvious challenge, few HIV self-disclosure models exist. Objectives This study was aimed at developing a self-disclosure model that would assist adolescents with perinatally acquired HIV in Eswatini to share their HIV status with others. Method The explanatory sequential mixed method design was used; therefore, quantitative data were collected first from 361 ALHIV aged 15–19 years using questionnaires and analysed. Qualitative data were collected from 23 ALHIV, 24 nurses and 4 policymakers using 3 focus group discussions and in-depth individual interviews. For quantitative data, statistical analysis was utilised, and grounded theory guided the analysis of qualitative data and the development of the model. Results HIV self-disclosure is the central concept for this model, and it is supported by four major concepts: (1) national HIV strategic framework, (2) enablers, (3) adolescent empowerment and (4) model outcomes. The description of the model was conducted using Chinn and Kramer’s stages of model development. Conclusion HIV education and social support are important in reducing stigma and discrimination in communities where adolescents reside. Prioritising the training of nurses and developing self-disclosure guidelines would lead to a remarkably increased level of adolescent HIV self-disclosure. Contribution The contribution of this study is that it is the first of its kind to develop an adolescent HIV self-disclosure model in Eswatini.